PERAN FRONT MASYARAKAT PEDULI LINGKUNGAN (FMPL) GILI TRAWANGAN MELALUI METODE PARTICIPATORY LEARNING AND ACTION (PLA) DALAM TATA KELOLA SAMPAH BERKELANJUTAN - Ita Selvia, Siska; Widiyanti, Astrini; Dwiyansaputra, Ramaditia; Kusuma, Fendi Putra; Tiara, Baiq Najwa (Universitas Mataram, 2025)
The waste problem on a small island, coupled with the pressure of popular tourism activities in Indonesia, has caused Gili Trawangan to face serious challenges in waste management and requires the active involvement of all relevant stakeholders. The Gili Trawangan Environmental Care Community Front (FMPL) is a self-help group. This community service activity aims to strengthen the role of the Gili Trawangan Environmental Care Community Front (FMPL) through the application of the Participatory Learning and Action (PLA) method in sustainable waste management. The PLA approach encourages the active participation of FMPL members in identifying problems, designing solutions, and implementing concrete actions appropriate to the local context. Activities are carried out through workshops, focus group discussions, and direct practice in the field. The results of the community service show an increase in the capacity of FMPL members in the aspects of planning, implementing, and evaluating waste management programs. In addition, a shared commitment is built among residents and local stakeholders to support a more sustainable waste management system. This activity positively contributes to strengthening community institutions and improving environmental quality in Gili Trawangan